FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN PADA BENGKEL SURABAYA BAN TULUNGAGUNG - Husna, Ahdiyan Nurfi; Ichsannudin; Ratnanto , Sigit (Universitas Nusantara PGRI Kediri, 2021)
Abstract The purpose of this study is to analyze how the influence of Engagement, Quality Service, and Perception Price on customer satisfaction at Bengkel Surabaya Tires Tulungagung either partially or simultaneously. The population in this study were all consumers of Bengkel Surabaya Tires Tulungagung. In this study, samples were taken as many as 40 respondents from an unlimited number of populations. The sampling technique used is accidental sampling. The results showed that there was a significant influence between Engagement, Quality Service, and Perception Price, either partially or simultaneously on customer satisfaction at Bengkel Surabaya Tires Tulungagung. Keywords: Engagement, Quality Service, Perception Price, and Customer Satisfaction Abstrak Tujuan penelitian ini untuk menganalisis bagaimana pengaruh Engagement, Quality Service, Dan Perception Price Terhadap Kepuasan pelanggan pada Bengkel Surabaya Ban Tulungagung baik secara parsial maupun simultan. Populasi dalam penelitian ini adalah seluruh konsumen Bengkel Surabaya Ban Tulungagung. Dalam penelitian ini sampel yang diambil sebanyak 40 orang responden dari jumlah populasi yang tidak terbatas. Teknik pengambilan sampel yang digunakan adalah accidental sampling. Hasil penelitian menunjukkan bahwa ada pengaruh yang signifikan antara Engagement, Quality Service, Dan Perception Pricebaik secara parsial maupun simultan terhadap kepuasan pelanggan pada Bengkel Surabaya Ban Tulungagung. Keywords: Engagement, Quality Service, Perception Price, dan Kepuasan Abstract The purpose of this study is to analyze how the influence of Engagement, Quality Service, and Perception Price on customer satisfaction at Bengkel Surabaya Tires Tulungagung either partially or simultaneously. The population in this study were all consumers of Bengkel Surabaya Tires Tulungagung. In this study, samples were taken as many as 40 respondents from an unlimited number of populations. The sampling technique used is accidental sampling. The results showed that there was a significant influence between Engagement, Quality Service, and Perception Price, either partially or simultaneously on customer satisfaction at Bengkel Surabaya Tires Tulungagung. Keywords: Engagement, Quality Service, Perception Price, and Customer Satisfaction Abstrak Tujuan penelitian ini untuk menganalisis bagaimana pengaruh Engagement, Quality Service, Dan Perception Price Terhadap Kepuasan pelanggan pada Bengkel Surabaya Ban Tulungagung baik secara parsial maupun simultan. Populasi dalam penelitian ini adalah seluruh konsumen Bengkel Surabaya Ban Tulungagung. Dalam penelitian ini sampel yang diambil sebanyak 40 orang responden dari jumlah populasi yang tidak terbatas. Teknik pengambilan sampel yang digunakan adalah accidental sampling. Hasil penelitian menunjukkan bahwa ada pengaruh yang signifikan antara Engagement, Quality Service, Dan Perception Pricebaik secara parsial maupun simultan terhadap kepuasan pelanggan pada Bengkel Surabaya Ban Tulungagung. Keywords: Engagement, Quality Service, Perception Price, dan Kepuasan pelanggan